Children, parents and anxiety - Toshiyuki Moro, Eduardo [UNESP] (2004)
BACKGROUND AND OBJECTIVES: Preoperative pediatric anxiety is characterized by stress, worry, nervosism and concern and may be expressed in different ways. Postoperative behavior changes, such as nocturnal enuresis, dietary problems, apathy, insomnia, nightmares and agitated sleep may be results of this anxiety. In some children, these changes persist for one year. This study aimed at evaluating anxiety-related aspects affecting children and parents in the preoperative period, as well as pharmacological or non-pharmacological interventions to minimize them. CONTENTS: The relationship between preoperative anxiety in children and postoperative behavior changes, as well as the influence of variables such as age, temperament, previous hospital experience and pain are discussed. Approaches to decrease children's preoperative anxiety, such as the presence of parents during anesthetic induction or information programs and preanesthetic medication are reviewed. CONCLUSIONS: The preoperative period is accompanied of an emotional overload for the whole family, especially the child. For many children, a turbulent preoperative period may translate into several behavior changes lasting for long periods of time. The presence of parents during anesthetic induction and the preoperative preparation of children and parents may be useful for selected cases, taking into account age, temperament and previous hospital experience. Preanesthetic medication with benzodiazepines, especially midazolam, is clearly the most effective method to decrease postoperative anxiety in children and their related behavior changes.